Genetic prioritisation of candidate drug targets for glaucoma through multi-trait and multi-omics integration - Jianqi Chen; Yangjiani Li; Yingting Zhu; Zhidong Li; Shitong Huang; Wenzhi Huang; Yuyao Ling; Jingying Liang; Yunxia Leng; Yehong Zhuo (Eye and Vision)
Abstract Background Glaucoma causes permanent blindness. Current treatments have limited effectiveness, necessitating novel therapeutic strategies. We aimed to identify potential drug targets for glaucoma by integrating multi-trait and multi-omic analyses. Methods We sourced druggable gene expression and protein abundance summary-level data from quantitative trait loci studies, and genetic associations with glaucoma from a large-scale multi-trait analysis. We employed proteome and transcriptome Mendelian randomization (MR) and colocalisation to identify potential therapeutic targets, glaucoma endophenotype MR to explore the potential mechanisms of identified associations, and phenome-wide MR to investigate possible adverse effects of candidate targets. Results We identified CPXM1 and FLT4 as tier 1; INSR as tier 2; and CPZ and PXDN as tier 3 druggable genes. Genetically predicted higher levels of CPXM1 [odds ratio (OR): 0.86, 95% confidence interval (CI): 0.81–0.91, P FDR < 0.001], FLT4 (OR: 0.74, 95% CI: 0.64 − 0.87, P FDR = 0.033), INSR (OR: 0.58, 95% CI: 0.43 − 0.78, P FDR = 0.042), and CPZ (OR: 0.55, 95% CI: 0.40 − 0.74, P FDR = 0.033) were associated with decreased glaucoma risk while those of PXDN (OR: 1.33, 95% CI: 1.15 − 1.54, P FDR = 0.033) with increased risk. The associations for CPXM1 (OR: 0.53, 95% CI: 0.39 − 0.73, P < 0.001) and FLT4 (OR: 0.86, 95% CI: 0.78 − 0.95, P = 0.005) were confirmed transcriptome-wide and colocalisation was confirmed for CPXM1 [posterior probability H4 (PPH4) = 0.940], FLT4 (PPH4 = 0.701), and INSR (PPH4 = 0.706). The protective effects of CPXM1 and CPZ may be attributed to intraocular pressure-lowering activities. The risk associated with PXDN is due to its involvement in glaucomatous neuropathy. No significant adverse effects were identified. Conclusions This study provides novel insights into glaucoma pathophysiology and promotes pharmaceutical target innovation.